(untitled) - Toynbee, Arnold (New York, 1948)
Arnold Toynbee's A Study of History is a six-volume analysis of the rise and fall of human civilizations
Keywords: Civilization,Văn minh,History,Lịch sử; Philosophy,Lý luận